Health care setting and severity, symptom burden, and complications in patients with Philadelphia-negative myeloproliferative neoplasms (MPN): a comparison between university hospitals, community hospitals, and office-based physicians - Kaifie, Andrea; Isfort, S.; Gattermann, N.; Hollburg, W.; Klausmann, M.; Wolf, D.; Maintz, C.; Hänel, M.; Goekkurt, E.; Göthert, J. R.; Platzbecker, U.; Geer, T.; et al. (Annals of Hematology, 2016)
Philadelphia-negative myeloproliferative neoplasms (MPN) comprise a heterogeneous group of chronic hematological malignancies with significant variations in clinical characteristics. Due to the long survival and the feasibility of oral or subcutaneous therapy, these patients are frequently treated outside of larger academic centers. This analysis was performed to elucidate differences in MPN patients in three different health care settings: university hospitals (UH), community hospitals (CH), and office-based physicians (OBP). The MPN registry of the Study Alliance Leukemia is a non-interventional prospective study including adult patients with an MPN according to WHO criteria (2008). For statistical analysis, descriptive methods and tests for significant differences were used. Besides a different distribution of MPN subtypes between the settings, patients contributed by UH showed an impaired medical condition, a higher comorbidity burden, and more vascular complications. In the risk group analyses, the majority of polycythemia vera (PV) and essential thrombocythemia (ET) patients from UH were classified into the high-risk category due to previous vascular events, while for PV and ET patients in the CH and OBP settings, age was the major parameter for a high-risk categorization. Regarding MPN-directed therapy, PV patients from the UH setting were more likely to receive ruxolitinib within the framework of a clinical trial. In summary, the characteristics and management of patients differed significantly between the three health care settings with a higher burden of vascular events and comorbidities in patients contributed by UH. These differences need to be taken into account for further analyses and design of clinical trials.
CRIS-Team Scopus Importer:2023-09-25
Keywords: Comorbidities; Essential thrombocythemia; Myeloproliferative neoplasms (MPN); Polycythemia vera; Primary myelofibrosis; Vascular events